Study of Coffee Plant Propagation (Coffea spp) with Leaf Cut - Budiman Setiawan; Ahmad Rafiqi Tantawi; Azhari Azhari (Budapest International Research and Critics University, 2019)
Coffee (Coffea spp) is mostly useful as a beverage is not foreign not only for the nation of Indonesia, but also for various nations in the world. One way to increase yields and extend the life of coffee plants is by pruning. From the results of this pruning of course produces quite a lot of leaves are wasted, so it takes science and technology cultivation of coffee plants by utilizing the coffee leaves. In this study will discuss about the Study of Coffee Plant Propagation (Coffea spp) With Leaf Cut. The research was conducted in March - June 2011 in Galang Suka Village, Galang Subdistrict, Deli Serdang Regency. This research was conducted by Randomized Complete Design (RAL) Factorial with two factors. The first factor is a coffee leaf (D) consisting of two levels of treatment. D1 = The base of the leaf without the petiole, D2 = Leaf tip. The second factor is Nutrition (N) which consists of six levels of treatment. N0 = Rotone-F 200 mg / l, N3 = Growtone 200 mg / l, N4 = Growtone 300 mg / l, N5 = Dekamon 2 cc / 10 liters. From the results of the study it can be concluded that leaf tip (D2) cuttings given Growtone 200 mg / l (N3D2) survive until the end of the study, as well as leaf tip (D2) cuttings given Dekamon 2cc / 10 l (N5D2) although the numbers are only 1.23 and 1.06 and N3D2 is better than N5D2.